Gene therapy: A Revolution in Medicine or a Risky Game with our DNA? - Kozakiewicz, Julia; Okońska, Aleksandra; Kościelecki, Kamil; Kalisz, Agnieszka; Skorulska, Iwona; Mączewska, Klaudia; Długozima, Patrycja; Grzeszczuk, Paulina; Grywińska, Weronika; Głowacka, Aleksandra (Quality in Sport, 2025)
Introduction: The aim of this review is to provide an overview of the applications of gene therapies in various diseases and to highlight areas where further research is needed. Materials and methods: A review of chosen literature in the PubMed database was conducted, using the following keywords: ,,gene therapy”, “SMA”, “DMD”, “Parkinson’s Disease”, “Huntington’s disease” Summary: Gene therapy can be useful in a variety of medical conditions, including Parkinson’s disease, pulmonary hypertension, Wiskott-Aldrich syndrome, spinal muscular atrophy (SMA), Huntington’s disease, Duchenne muscular dystrophy (DMD), and chronic pain management. Different gene therapy approaches, such as viral vector delivery, CRISPR-Cas9 gene editing, exon-skipping therapy, and antisense oligonucleotides (ASOs), have demonstrated potential in treating these diseases. Conclusions: Gene therapy represents a groundbreaking advancement in medicine, offering hope for diseases that were once considered untreatable. Clinical trials have demonstrated encouraging outcomes in treating neurodegenerative and genetic disorders. Future developments in gene editing tools, improved vector systems, and targeted delivery methods will be crucial in enhancing the efficacy of gene therapy.